Aboveground Biomass Along an Elevation Gradient in an Evergreen Andean–Amazonian Forest in Ecuador - Maza, Byron; Rodes-Blanco, Marina; Rojas, Edison (Frontiers in Forests and Global Change, 2022)
The aim of this research was to assess how aboveground biomass changes along an altitudinal gradient in evergreen Andean - Amazonian forests (Evergreen Lower Montane Forest, north - eastern Cordillera of the Andes; Evergreen Piedmont Forest, north-eastern Cordillera of the Andes; and Evergreen Lowland Forest, Napo-Curaray) from 373 to 1826 meters above sea level. All trees measured in nine permanent 0.36 ha plots (60 m × 60 m) were ≥ 10 cm (diameter at breast height) in the aforementioned ecosystems. We assessed tree density, basal area, species richness and aboveground biomass. In the tree inventory, we measured 2132 trees (Lower Montane Forest 687, Piedmont Forest 773 and Lowland Forest 672). Aboveground biomass (Mg ha-1) increases with decreasing elevations: 310.26 ± 81.59 (SD) for the Evergreen Lower Montane Forest, 347.73 ± 90.38 (SD) for the Evergreen Piedmont Forest and 377.39 ± 42.73 (SD) for the Evergreen Lowland Forest. Otoba glycycarpa and Alchornea latifolia were the species with the highest biomass importance value in the Evergreen Lower Montane Forest (1421-1826 m.a.s.l.), Spirotheca rosea and Pouteria glomerata in the Evergreen Piedmont Forest (892-1195 m.a.s.l.), Otoba glycycarpa and Iriartea deltoidea in Evergreen Lowland Forest (373-394 m.a.s.l.). Biomass contribution along the altitudinal gradient in the evergreen Andean - Amazonian forests is concentrated in few species. This has implications in forest management and reforestation programs where the main focus is on carbon sequestration.